Netradiční studenti pedagogických oborů na českých vysokých školách - Novotný, Petr (Masaryk University Press, 2021)
Title in English: Non-traditional students studying education in Czech universities. This publication is devoted to the topic of non-traditional students in tertiary education. The key criteria for our definition of this group are age and a break in the formal educational trajectory after high school. From among all the non-traditional students in Czech higher education, we selected those who chose university studies in study programs that qualify them for work in education (e.g., teachers, counsellors, youth workers, teacher assistants, social educators, and adult educators). The book is divided into 11 interconnected chapters presenting theoretical background, methodology and results of mixed design research conducted by the team of authors.